University students' perspectives on Interprofessional Education (Research, Society and Development, 2021)
This research aimed to evaluate the perspective of health students on interprofessional education at a public university in the state of Maranhão. A questionnaire was applied with sociodemographic and profile variables of the students and the RIPLS (Readiness for Interprofessional Learning Scale) instrument adapted online with 254 students from the health courses. For the analysis of the statistically significant difference, Student's t test and Anova were calculated for the difference in means and Chi-square for the agreement of the statements alone, considering the significance level of 5%, being analyzed in the Stata version 14 program. results identified that there is a high availability of students of health courses for interprofessional learning, being more accepted in clinical periods / intermediate phase of courses, where it is suggested that collaborative practices will be more required. It is noteworthy that the majority of those surveyed are in a Comfort Zone in relation to Interprofessional Education and Collaborative Practices in the academic environment. The study highlights that extracurricular activities are indispensable tools in the teaching-learning process of interprofessional education and collaborative practices. It concludes the importance of creating and maintaining environments that address the discussion of this theme, so that the collaborative interprofessional practice occurs comprehensively among all students of health courses.